Purchase Decisions through EWOM and Risk Perception - Setiawan, Rahyuniati; Saepuloh, Asep; Nugraha, Sukma (Jurnal Inovasi Bisnis dan Kewirausahaan, 2023)
This research explores the impact of electronic word of mouth (e-WOM) and risk perception on purchasing decisions within the marketplace among residents in Garut Regency. The study focuses on individuals who have engaged in shopping activities on various platforms such as Shopee, Tokopedia, Lazada, Bukalapak, Blibli, and others in Garut Regency. The research population consists of individuals who have actively participated in marketplace transactions, with a sample size of 96 marketplace customers. Data collection utilized two methods: online surveys via Google Form and offline surveys conducted by directly engaging respondents across various sub-districts in Garut Regency. Data analysis was carried out using SPSS Statistics 26 and SmartPLS3 applications, employing purposive sampling. The primary objective of this research is to ascertain the influence of electronic word of mouth (e-WOM) and risk perception on purchasing decisions. The findings reveal that the e-WOM variable holds a substantial influence of 63% on purchasing decisions, while the risk perception variable exerts an 18.4% influence. These results demonstrate the interconnected nature of these variables, indicating that each variable can significantly impact the others.